Exploring challenges and strategies in English speaking among Indonesian university students: A case study of AKM university - Anggrisia, Nur Fitria; Robah, Asna (Universitas Islam Negeri Banda Aceh, 2023)
English language education in Indonesia spans from primary school to university levels. However, achieving mastery in English, particularly in speaking, remains a significant challenge for Indonesian university students. This study aimed to investigate the problems faced by these students in speaking English and describe their efforts to overcome this deficiency. The research utilized a descriptive qualitative method, employing questionnaires and interviews as instruments. The study participants consisted of 45 second-semester students from the English Education Department at AKM University (pseudonym). The findings revealed that students encountered both linguistic and psychological challenges when speaking English. Linguistic problems included confusion in tense usage, a lack of grammar understanding, and difficulty in selecting appropriate vocabulary. Psychological issues encompassed feelings of nervousness, lack of confidence, fear of making mistakes, and the fear of being laughed at. Furthermore, insufficient practice emerged as an environmental factor contributing to speaking difficulties. To address these challenges, students adopted various learning strategies proposed by Oxford (1990), including memory strategies, cognitive strategies, metacognitive strategies, affective strategies, and social strategies.